A Formation of Cloud Data Sharing With Integrity and User Revocation (International Journal of Engineering and Computer Science, 2017)
Cloud computing and storage services, data is not only stored in the cloud, but routinely shared among a large number of users in a group. It remains elusive, however, to design an efficient mechanism to audit the integrity of such shared data, while still preserving identity privacy. In this paper, we propose Knox, a privacy-preserving auditing mechanism for data stored in the cloud and shared among a large number of users in a group. In particular, we utilize group signatures to construct homomorphic authenticators, so that a third party auditor (TPA) is able to verify the integrity of shared data for users without retrieving the entire data. Meanwhile, the identity of the signer on each block in shared data is kept private from the TPA. With Knox, the amount of information used for verification, as well as the time it takes to audit with it, are not affected by the number of users in the group. In addition,Knox exploits homomorphic MACs to reduce the space used to store such verification information. Our experimental results show that Knox is able to efficiently audit the correctness of data, shared among a large number of users.